Pregnancy outcome in women with antiphospholipid syndrome and alloimmunity: a case report - Ospina, Serguei Abel Castañeda; Maya, Wálter Darío Cardona; Sánchez, Julio César Bueno; Jaramillo, Ángela Patricia Cadavid (São Paulo Medical Journal, 2003)
CONTEXT: Patients with antiphospholipid syndrome and alloimmunity have poor pregnancy outcomes. Several diagnostic and therapeutic options exist for these disorders, although there is no consensus as to the best treatment. CASE REPORT: We present here the clinical course and treatment of a woman with a history of two miscarriages who joined our program 10 years ago and has been followed up ever since. After antiphospholipid syndrome and alloimmune failure were diagnosed, she was given preconceptional treatment using unfractionated heparin, aspirin, prednisone and lymphocyte immunizations. She delivered two premature babies in the following two pregnancies. At present both children are healthy and are attending school. The fifth pregnancy was unsuccessful, in spite of having undergone a similar but postconceptional therapeutic scheme. We discuss this case focusing on the pathogenic mechanisms and the therapeutic aspects of these disorders.